Antibacterial Activity of Limau Kuit (Citrus hystrix DC.) Leaf Essential Oil Against Methicillin-Resistant Staphylococcus aureus and Multidrug-Resistant Pseudomonas aeruginosa - Leka Lutpiatina; Fitria Audrey Mau'izah; Wina Fitria; Ratih Dewi Dwiyanti; Aima Insana (Baiman Bauntung Batuah Center, 2026)
Antibiotic resistance in pathogenic bacteria, including Methicillin-resistant Staphylococcus aureus (MRSA) and Multi-drug-resistant Pseudomonas aeruginosa (MDR P. aeruginosa), has encouraged the development of alternative antibacterial agents from natural sources. This study aimed to analyse the antibacterial Activity of Limau Kuit (Citrus hystrix DC.) leaf essential oil against MRSA and MDR P. aeruginosa. The study used a true experimental design with a posttest-only control group design. The essential oil was obtained through steam-water distillation of Limau Kuit leaves and then tested at concentrations of 50%, 60%, 70%, 80%, 90%, and 100% using the well diffusion method. Positive controls included ciprofloxacin and ceftazidime, while dimethyl sulfoxide served as the negative control. Each treatment was repeated four times. Data were analysed using Welch ANOVA and Games-Howell tests for MRSA and Kruskal-Wallis and Mann-Whitney tests for MDR P. aeruginosa. The essential oil yield was 0.60% (v/w). All concentrations showed antibacterial activity against both test bacteria. The largest inhibition zone diameter against MRSA was obtained at 90% (22.23 ± 1.75 mm), while against MDR P. aeruginosa at 80% (13.98 ± 1.48 mm). Statistical analysis showed a significant difference between concentrations in MRSA (p < 0.001) and MDR P. aeruginosa (p = 0.003). Antibacterial activity against MRSA is higher than against MDR P. aeruginosa, which is thought to be related to differences in cell wall structure and resistance mechanisms of the two bacteria. Lime leaf essential oil has potential as a natural antibacterial against antibiotic-resistant bacteria. However, further research is needed to determine active compound content, mechanism of action, and the minimum inhibitory concentration and minimum bactericidal concentration.